PREPARATION OF ANTI-IDIOTYPE ANTIBODY AS DIAGNOSTIC KIT IN RABIES SEROLOGICAL TEST - SAYU P.Y. PARYATI; EKA N. NAWANGSIH; IIS I. RAKHMAT (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
Serology remains the only way to monitor the effectiveness of vaccination of humans and animals against rabies. Many techniques for determining the level of rabies antibodies have been described, and all of the methods used rabies viruses as antigen. Indeed attenuated viruses can revert to a more virulent form, and inactivated virus may produce serious side effects. Anti-idiotype Ab can induce protective immune response against rabies virus, its means that anti-idiotype Ab can be used as surrogate antigen in serological test.The aim of this study is to prepare the anti-idiotype antibody (anti-idiotype Ab) as diagnostic kit in rabies serological test. Polyclonal anti-idiotype Ab were prepared in laying chickens and purified using affinity chromatography column for IgY. Rabbit anti dog immunoglobuline were prepared used New Zeeland White strain, and dog anti rabies serum were prepared from rabies immunized dog. For the preparation of the kit, it takes a few stages, i.e. the making of stocks A, stocks B and prototype diagnostic kit. Stocks A is a mixture of S. aureus Cowan I intact in solution of Tris Buffer HCl with rabbit anti dog serum in various comparisons (v/v). Stocks B is a mixture of rabies anti-idiotype Ab with rabies antibody (IgG anti rabies) are harvested from dog.Comparison of the obtained between whole S. aureus Cowan I and rabbit serum anti dog is 4~6:2~4. Optimization of stocks A and B based on the principle as follows: a merger of stocks A and B must not cause coagglutination. Formulation of aqueous stocks A and B will be a candidate when the diagnostic kits on the positive control produces coagglutination and negative controls do not produce coagglutination. The conclusions of this study is the anti-idiotype antibody can used and prepared as kit diagnostic with the principle of coagglutination by utilizing A protein of S. aureus.